Therapeutic potential of selective serotonin reuptake inhibitor and anti-inflammatory COX-2 inhibitors drugs for epilepsy (Research, Society and Development, 2022)
Epilepsy is a neurological disease caused by disturbances in the electrical propagation between neurons, which causes great damage to patients' lives, and can even lead to death. There are several proposals to understand its biochemical functioning, so current pharmacological treatments are based on the interruption of electrical conduction or modulation of neurotransmitters, such as phenobarbital and phenytoin. Thus, the present work aims to analyze the therapeutic potential of drugs such as COX-2 inhibitors and selective serotonin reuptake inhibitors (SSRIs) in the control of epilepsy. Thus, a narrative review of the literature was carried out using the “PubMed” database in order to find the theoretical bases and experimental works that demonstrate the mechanism of such drugs. The work concludes that SSRIs and COX-2 inhibitors have several mechanisms that can theoretically treat epilepsy, this is due to the establishment of a higher concentration of the neurotransmitter serotonin, as well as a reduction in the formation of quinolinic acid, which is a potential neurotoxic agent. which contributes to epileptogenesis.